Solid-state electrolyte, preparation method thereof and application of solid-state electrolyte in solid-state lithium battery
By using Ce and Nb double-doped nanosheet barium titanate BaTiO3 as an inorganic filler in the composite solid electrolyte, combined with a polymer matrix and lithium salt, the problem of easy agglomeration of inorganic nanoparticles during the preparation process of the composite solid electrolyte is solved and achieved Comprehensive properties of high ionic conductivity, wide electrochemical window, high mechanical strength and good interfacial compatibility.
Patent Information
- Application Number
- CN202411442284.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-16
AI Technical Summary
During the preparation process of existing composite solid electrolytes, there is a problem that inorganic nanoparticles are prone to agglomeration, and the preparation process is complex, making it difficult to achieve comprehensive performance of high ionic conductivity, wide electrochemical windows, high mechanical strength and good interface contact.
Ce and Nb double-doped nanosheet barium titanate BaTiO3 was used as an inorganic filler, combined with a polymer matrix and lithium salt, and a composite solid-state electrolyte was prepared through microwave reaction and heat treatment. This method destroys the lattice structure of barium titanate by doping elements, creates oxygen vacancy defects, improves the ionic conductivity of the electrolyte, and forms a three-dimensional grid structure through the nanosheet structure to enhance lithium ion conductivity.
It achieves high ionic conductivity, wide electrochemical window, high mechanical strength and good interface compatibility of the composite solid electrolyte, effectively inhibits the growth of lithium dendrites and improves the electrochemical stability and thermal stability of the battery. At the same time, the preparation process is simple and suitable for large-scale industrial production.
Smart Images

Figure CN119340461A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte and a preparation method thereof. Background Art
[0002] The rapid development of new energy vehicles and 5G communication technology has put forward higher requirements on the safety, energy density and cycle performance of lithium-ion batteries. At present, commercially available lithium-ion batteries mainly use liquid electrolytes. Liquid electrolytes have the advantages of high conductivity and excellent electrode wetting ability, but they also have safety issues such as easy leakage, corrosion and easy combustion. Compared with liquid electrolytes, solid electrolytes have the advantages of stable structure, good mechanical properties and non-flammability. Replacing liquid electrolytes with solid electrolytes can effectively solve the safety problems of liquid lithium batteries. According to the composition of solid electrolytes, they can be divided into inorganic solid electrolytes, polymer solid electrolytes and composite solid electrolytes.
[0003] Inorganic solid electrolytes have high ionic conductivity, electrochemical stability window and mechanical strength, but the solid / solid contact resistance between the electrode and the electrolyte is large, and the processing is difficult and costly. Polymer solid electrolytes have good flexibility, processability and contact interface performance, but the room temperature ionic conductivity is low and they need to operate at high temperatures. Composite solid electrolytes are a promising alternative, generally obtained by combining inorganic fillers and polymer solid electrolytes. They have both the high ionic conductivity of inorganic solid electrolytes and the good flexibility of polymer solid electrolytes, and have become one of the current research hotspots. The solid electrolyte obtained by adding inorganic fillers to polymer solid electrolytes has excellent comprehensive properties. Inorganic fillers can play three roles: reduce crystallinity, increase amorphous phase area, and facilitate lithium ion migration; fast lithium ion channels can be formed near filler particles; and increase the mechanical properties of the polymer matrix, making it easy to form a film. Composite solid electrolytes formed by comprehensive utilization of the high ionic conductivity and good mechanical strength of inorganic materials and the good interface compatibility and electrochemical stability of polymer materials can effectively improve lithium ion conductivity, inhibit the growth of lithium dendrites during battery operation, and improve the electrochemical stability and thermal stability of the battery as well as the Coulombic efficiency. However, there are still a series of technical problems to be solved in the research of composite solid electrolytes. For composite solid electrolytes, how to prepare composite electrolytes with high ionic conductivity, wide electrochemical window, high mechanical strength and taking into account interface contact and interface compatibility is the current research focus.
[0004] The invention patent with announcement number CN107834104B discloses a composite solid electrolyte, a preparation method thereof, and an application in an all-solid-state lithium battery. The composite solid electrolyte comprises polyethylene oxide, polyvinylidene fluoride or its derivatives, lithium salts, and inorganic nanoparticles. The composite solid electrolyte has high mechanical properties and excellent electrochemical stability. The assembled battery has stable cycle performance and high capacity. However, the problem of easy agglomeration of inorganic nanoparticles still exists.
[0005] The invention patent with announcement number CN117352827B discloses an organic-inorganic composite solid electrolyte constructed by using Nb and Al dual-doped garnet ceramic fiber-based composite solid electrolyte (LALZNO) nanofibers as inorganic fillers, PVDF-HFP as polymer substrate, and lithium bistrifluoromethanesulfonyl imide (Li TFS I) as lithium salt prepared by electrospinning technology; the porous nanofiber rod-like structure LALZNO prepared by electrospinning and high-temperature calcination aims to improve the ionic conductivity and ion migration number of the polymer solid electrolyte, enhance the lithium cycle stability, and ultimately achieve stable cycling of lithium iron phosphate (LFP) batteries; however, the preparation process of the above-mentioned composite solid electrolyte is complicated. Summary of the invention
[0006] In view of the above technical problems, the present invention provides a composite solid electrolyte and a preparation method thereof.
[0007] A composite solid electrolyte comprises Ce and Nb doped nanosheet barium titanate BaTiO3, a polymer matrix and a lithium salt. The preparation method of the composite solid electrolyte comprises the following steps:
[0008] (1) adding a titanium source and a barium source into ethanol, stirring and mixing uniformly to obtain a mixed solution 1;
[0009] (2) adding the dopant Ce source and Nb source into ethanol, and continuing to stir and mix evenly to obtain a mixed solution 2;
[0010] (3) Mixing the mixed solutions 1 and 2, dropping a certain amount of ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 130-160° C. for 50-100 minutes; after the reaction is completed, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0011] (4) placing the obtained product in a tube furnace and heat treating it at 350-500° C. to obtain Ce and Nb doped nanosheet barium titanate BaTiO3;
[0012] (5) Ce and Nb doped nanosheet barium titanate BaTiO3, polymer and lithium salt are fully and evenly mixed with a solvent in a mass ratio of (1-20): (30-90): (5-15) to obtain a mixed solution; the stirred mixed solution is coated to form a film, and the solvent is dried to obtain a composite solid electrolyte.
[0013] In some preferred embodiments of the present invention, the titanium source is one or more of titanium tetrachloride, isopropyl titanate, and tetrabutyl titanate; the barium source is one or more of barium nitrate and barium chloride;
[0014] In some preferred embodiments of the present invention, the molar ratio of the titanium source to the barium source is 1:1;
[0015] In some preferred embodiments of the present invention, the Ce source is cerium nitrate or cerium chloride; the Nb source is niobium nitrate, niobium acetate or niobium oxalate;
[0016] In some preferred embodiments of the present invention, the molar ratio of titanium source: Ce source: Nb source is 1: (0.01-0.03): (0.01-0.03);
[0017] In some preferred embodiments of the present invention, the molar ratio of titanium source: ammonium nitrate is 1:(1-2);
[0018] In some preferred embodiments of the present invention, the lithium salt includes one or more of LiClO4, LiBF4, LiBOB, LiTFSI;
[0019] In some preferred embodiments of the present invention, the polymer is PEO or PVDF;
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0021] (1) This application proposes for the first time a Ce and Nb doped nanosheet barium titanate BaTiO3. The doping of Ce and Nb elements, on the one hand, enters the BaTiO3 lattice, destroying the original lattice order of barium titanate, thereby generating a large number of oxygen vacancy defects, thereby improving the ionic conductivity of the electrolyte; in addition, it is found in the experimental process that Ce and Nb are conducive to the formation of nanosheets;
[0022] (2) The dual-doped nanosheets of barium titanate BaTiO3 overlap each other to form a three-dimensional grid structure, constructing a long-range ion transfer channel, greatly facilitating the shuttle of ions, thereby improving the lithium ion conductivity;
[0023] (3) The nanosheet structure can enhance the interfacial compatibility between the solid electrolyte and the electrode material, reduce the interfacial resistance, and effectively inhibit the growth of lithium dendrites.
[0024] (4) The preparation process of the invention is simple to operate and can be convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of the double-doped nanosheet barium titanate BaTiO3 of the present application;
[0026] Figure 2 The cycle performance diagram of button cells assembled with composite solid electrolyte membranes prepared in Example 1 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Example 1
[0029] A composite solid electrolyte, the preparation method comprises the following steps:
[0030] (1) Add 0.2 mol titanium tetrachloride and 0.2 mol barium nitrate into 80 mL ethanol, stir and mix well to obtain a mixed solution 1;
[0031] (2) adding 0.003 mol of cerium nitrate and 0.003 mol of niobium nitrate as dopants to 20 mL of ethanol, and continuing to stir and mix well to obtain a mixed solution 2;
[0032] (3) Mixing the mixed solutions 1 and 2, adding 0.2 mol ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 150° C. for 60 minutes; after the reaction, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0033] (4) The obtained product was placed in a tube furnace and kept at 350°C for 60 min to obtain Ce and Nb doped nanosheet barium titanate BaTiO 3;
[0034] (5) Ce and Nb doped nanosheet barium titanate BaTiO3, polymer PEO and lithium salt LiBF4 are fully and evenly mixed with 10 mL of acetonitrile in a mass ratio of 10:60:10 to obtain a mixed solution; the mixed solution is poured into a polytetrafluoroethylene mold to form a film, and the solvent is removed by drying to obtain a composite solid electrolyte.
[0035] Example 2
[0036] A composite solid electrolyte, the preparation method comprises the following steps:
[0037] (4) adding 0.2 mol titanium tetrachloride and 0.2 mol barium nitrate into 80 mL ethanol, stirring and mixing to obtain a mixed solution 1;
[0038] (5) Add 0.003 mol of cerium nitrate and 0.003 mol of niobium nitrate as dopants into 20 mL of ethanol, and continue to stir and mix to obtain a mixed solution 2;
[0039] (6) Mixing the mixed solutions 1 and 2, adding 0.2 mol ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 150° C. for 60 minutes; after the reaction, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0040] (4) The obtained product was placed in a tube furnace and kept at 400°C for 60 min to obtain Ce and Nb doped nanosheet barium titanate BaTiO 3;
[0041] (5) Ce and Nb doped nanosheet barium titanate BaTiO3, polymer PEO and LiBF4 are fully and evenly mixed with 10 mL of acetonitrile in a mass ratio of 10:70:10 to obtain a mixed solution; the mixed solution is poured into a polytetrafluoroethylene mold to form a film, and the solvent is removed by drying to obtain a composite solid electrolyte.
[0042] Example 3
[0043] A composite solid electrolyte, the preparation method comprises the following steps:
[0044] (1) Add 0.2 mol titanium tetrachloride and 0.2 mol barium nitrate into 80 mL ethanol, stir and mix well to obtain a mixed solution 1;
[0045] (2) adding 0.002 mol of cerium nitrate and 0.002 mol of niobium nitrate as dopants to 20 mL of ethanol, and continuing to stir and mix to obtain a mixed solution 2;
[0046] (3) Mixing the mixed solutions 1 and 2, adding 0.2 mol ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 150° C. for 60 minutes; after the reaction, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0047] (4) The obtained product was placed in a tube furnace and kept at 400°C for 60 min to obtain Ce and Nb doped nanosheet barium titanate BaTiO 3;
[0048] (5) Ce and Nb doped nanosheet barium titanate BaTiO3, polymer PEO and LiBF4 were fully and evenly mixed with 10 mL of acetonitrile in a mass ratio of 10:60:10 to obtain a mixed solution; the mixed solution was poured into a polytetrafluoroethylene mold to form a film, and the solvent was removed by drying to obtain a composite solid electrolyte.
[0049] Example 4
[0050] A composite solid electrolyte, the preparation method comprises the following steps:
[0051] (1) Add 0.2 mol titanium tetrachloride and 0.2 mol barium nitrate into 80 mL ethanol, stir and mix well to obtain a mixed solution 1;
[0052] (2) adding 0.002 mol of cerium nitrate and 0.002 mol of niobium nitrate as dopants to 20 mL of ethanol, and continuing to stir and mix to obtain a mixed solution 2;
[0053] (3) Mixing the mixed solutions 1 and 2, dropping 0.3 mol ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 150° C. for 60 minutes; after the reaction, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0054] (4) The obtained product was placed in a tube furnace and kept at 400°C for 60 min to obtain Ce and Nb doped nanosheet barium titanate BaTiO 3;
[0055] (5) Ce and Nb doped nanosheet barium titanate BaTiO3, polymer PEO and LiBF4 were fully and evenly mixed with 10 mL of acetonitrile in a mass ratio of 10:60:10 to obtain a mixed solution; the mixed solution was poured into a polytetrafluoroethylene mold to form a film, and the solvent was removed by drying to obtain a composite solid electrolyte.
[0056] Comparative Example 1
[0057] A composite solid electrolyte, the preparation method comprises the following steps:
[0058] (1) Add 0.2 mol titanium tetrachloride and 0.2 mol barium nitrate into 80 mL ethanol, stir and mix well to obtain a mixed solution 1;
[0059] (2) adding 0.006 mol of dopant niobium nitrate into 20 mL of ethanol and continuing to stir and mix well to obtain a mixed solution 2;
[0060] (3) Mixing the mixed solutions 1 and 2, dropping 0.2 mol ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 150° C. for 60 minutes; after the reaction, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0061] (4) The obtained product was placed in a tube furnace and kept at 350°C for 60 min to obtain Nb-doped barium titanate BaTiO 3;
[0062] (5) Nb-doped barium titanate BaTiO3, polymer PEO and LiBF4 were fully and evenly mixed with 10 mL of acetonitrile in a mass ratio of 10:60:10 to obtain a mixed solution; the mixed solution was poured into a polytetrafluoroethylene mold to form a film, and the solvent was removed by drying to obtain a composite solid electrolyte.
[0063] Comparative Example 2
[0064] A composite solid electrolyte, the preparation method comprises the following steps:
[0065] (1) Add 0.2 mol titanium tetrachloride and 0.2 mol barium nitrate into 80 mL ethanol, stir and mix well to obtain a mixed solution 1;
[0066] (2) adding 0.006 mol of cerium nitrate as a dopant into 20 mL of ethanol and continuing to stir and mix well to obtain a mixed solution 2;
[0067] (3) Mixing the mixed solutions 1 and 2, dropping 0.2 mol ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 150° C. for 60 minutes; after the reaction, ultrasonically cleaning the product with deionized water and ethanol in turn;
[0068] (4) placing the obtained product in a tube furnace and maintaining the temperature at 350° C. for 60 min to obtain Ce-doped barium titanate BaTiO3;
[0069] (5) Ce-doped barium titanate BaTiO3, polymer PEO and LiBF4 were fully and evenly mixed with 10 mL of acetonitrile in a mass ratio of 10:60:10 to obtain a mixed solution; the mixed solution was poured into a polytetrafluoroethylene mold to form a film, and the solvent was removed by drying to obtain a composite solid electrolyte.
[0070] Electrochemical performance test:
[0071] Lithium iron phosphate, superconducting carbon black and PVDF were coated into films in a mass ratio of 80:10:10, dried and sliced as the positive electrode, and metallic lithium was used as the negative electrode. The composite solid electrolyte membrane prepared in Example 1 and the composite solid electrolyte membrane prepared in Comparative Examples 1-2 were used as the separator and electrolyte of the battery respectively, and button-type lithium-ion batteries were assembled in a glove box filled with argon gas. The electrochemical properties of the batteries were tested using a blue battery program-controlled tester. The results are shown in Table 1 and the attached drawings. Figure 2 .
[0072] Table 1
[0073] <![CDATA[Room temperature ionic conductivity (10 -3 S / cm)]]> Example 1 5.1 Comparative Example 1 4.3 Comparative Example 2 4.8
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a composite solid electrolyte, characterized in that : The composite solid electrolyte comprises Ce and Nb doped nanosheet barium titanate BaTiO3, a polymer matrix and a lithium salt; the preparation method comprises the following steps: (1) adding a titanium source and a barium source into ethanol, stirring and mixing uniformly to obtain a mixed solution 1; (2) adding the dopant Ce source and Nb source into ethanol, and continuing to stir and mix evenly to obtain a mixed solution 2; (3) Mixing the mixed solutions 1 and 2, adding a certain amount of ammonium nitrate to obtain a mixed solution 3, placing the mixed solution 3 in a microwave reactor, and reacting at 130-160° C. for 50-100 minutes; after the reaction is completed, ultrasonically cleaning the product with deionized water and ethanol in turn; (4) placing the obtained product in a tube furnace and heat treating it at 350-500° C. for 1-2 h to obtain Ce and Nb doped nanosheet barium titanate BaTiO3; (5) Ce and Nb doped nanosheet barium titanate BaTiO3, polymer and lithium salt are fully and evenly mixed with a solvent in a mass ratio of (1-20): (30-90): (5-15) to obtain a mixed solution; the mixed solution is stirred evenly, coated to form a film, and dried to remove the solvent to obtain a composite solid electrolyte.
2. According to the method for preparing a composite solid electrolyte according to claim 1, the titanium source is one or more of titanium tetrachloride, isopropyl titanate, and tetrabutyl titanate; the barium source is one or more of barium nitrate and barium chloride.
3. According to the method for preparing a composite solid electrolyte according to claim 1, the molar ratio of the titanium source to the barium source is 1:
1.
4. The method for preparing a composite solid electrolyte according to claim 1, wherein the Ce source is cerium nitrate or cerium chloride; and the Nb source is niobium nitrate, niobium acetate or niobium oxalate.
5. According to the method for preparing a composite solid electrolyte according to claim 1, the molar ratio of titanium source:Ce source:Nb source is 1:(0.01-0.03):(0.01-0.03).
6. The method for preparing a composite solid electrolyte according to claim 1, wherein the molar ratio of titanium source:ammonium nitrate is 1:(1-2).
7. The method for preparing a composite solid electrolyte according to claim 1, wherein the lithium salt comprises one or more of LiClO4, LiBF4, LiBOB, and Li TFS I.
8. The method for preparing a composite solid electrolyte according to claim 1, wherein the polymer is PEO or PVDF.
9. A composite solid electrolyte, characterized in that: Prepared by the method according to any one of claims 1 to 8.
10. Use of a composite solid electrolyte as claimed in claim 9, characterized in that: Apply it to solid-state batteries.
Citation Information
Patent Citations
Polymer-based composite solid electrolyte film and preparation method thereof
CN111403804A
Gel electrolyte as well as preparation method and application thereof
CN113130986A
Negative pole piece and preparation method thereof, battery and power utilization device
CN117497768A
Composite solid electrolyte ceramic chip and preparation method thereof
CN118239778A
High energy density ionic dielectric materials and devices
US20110212382A1